Saying What You Want: A Neuropragmatic Study of Telegraphic Directives and Theory of Mind in an Adolescent with ASD - Yanisha Dwi Astari; Armita Novriana Rambe; Ai Yeni Yuliyanti; Imam Muhtadi (Talenta Publisher, 2026)
Individuals with Autism Spectrum Disorder (ASD) frequently exhibit atypical pragmatic language patterns, yet the relationship between directive speech act production, telegraphic speech, and Theory of Mind (ToM) deficits remains underexplored from a neuropragmatic perspective. This qualitative case study investigated the directive utterances produced by a 15‑year‑old adolescent with ASD attending an inclusive classroom at SMPN 23 Padang, Indonesia. Data were collected over nine days of participant observation, video recordings, and the administration of the Sally-Anne false-belief test. A total of 140 directive utterances were analyzed using Ervin‑Tripp’s (1976) classification system. The results revealed that imperatives constituted most directive types (50%), followed by question directives (18.57%), hints (16.43%), permission directives (13.57%), and need statements (1.43%). No embedded imperatives were produced. The participant consistently employed telegraphic speech and failed the ToM test, indicating an inability to attribute false beliefs to others. From a neuropragmatic standpoint, these patterns – dominance of imperatives, absence of syntactically complex forms, and telegraphic reduction – suggest a delayed neurocognitive trajectory resembling that of typically developing children aged 2–6 years rather than intentional noncompliance. The findings imply that inclusive education practices should incorporate neuropragmatic awareness to better interpret and support the communicative intentions of adolescents with ASD.